Closing the Urban-Rural Power Divide - Hogan, Thor. author. aut Link
XI, 252 p. 22 illus.
Keywords: This book proposes a radical reorganization of political and electoral power to address the current political imbalance between urban and rural populations in the United States. Hogan argues that, despite being smaller in population, a “financialist-ruralist coalition” has effectively used the Constitution—especially equal representation in the Senate—to create an anti-urban “vetocracy.” This political imbalance protects the interests of the financial elite and rural cultural conservatives, while effectively blocking urban interests, particularly regarding the adoption of a broad range of structural reforms and progressive policy preferences. By re-dividing many of the largest federated states into smaller city-states, the book posits, the United States would reduce the ability of non-urban interests to control the Senate. This would allow an empowered urbanite alliance to pass the forward-looking legislation the nation needs to remain internationally competitive in the coming decades. Thor Hogan is a Professor of Politics and Environmental Sustainability at Earlham College, USA.